2003
DOI: 10.1093/jac/dkg325
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a cefoxitin 30  g disc on Iso-Sensitest agar for detection of methicillin-resistant Staphylococcus aureus

Abstract: We suggest that the cefoxitin method should replace that currently recommended by the SRGA for the detection of MRSA, and that it would fit well into BSAC methodology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
85
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(98 citation statements)
references
References 9 publications
8
85
0
5
Order By: Relevance
“…Thus, if there were changes in the cefoxitin breakpoints, the sensitivity of the method could be increased, perhaps without any decrease of specificity. Other authors have also suggested different breakpoints in the interpretative zone diameters of cefoxitin for better detection of methicillin resistance in S. aureus [7,10].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, if there were changes in the cefoxitin breakpoints, the sensitivity of the method could be increased, perhaps without any decrease of specificity. Other authors have also suggested different breakpoints in the interpretative zone diameters of cefoxitin for better detection of methicillin resistance in S. aureus [7,10].…”
Section: Resultsmentioning
confidence: 99%
“…Oxacillin-disk diffusion has been the traditional method for methicillin-resistance routine screening; but recently good accuracy of the cefoxitin disk for predicting methicillin resistance has been reported [4][5][6][7][8][9][10][11], and CLSI (Clinical and Laboratory Standards Institute) has recommended that cefoxitin should be preferred over oxacillin for the detection of mecA-mediated resistance [4]. However, the choice of the best phenotypic method for detecting methicillin resistance in S. aureus remains controversial.…”
mentioning
confidence: 99%
“…Errors in routine oxacillin susceptibility tests, including disc diffusion with either oxacillin or cefoxitin with different breakpoints, have also been reported elsewhere 4,8,14 . Laboratories may consider using two methods (cefoxitin disc plus oxacillin disc; or oxacillin agar plate plus disc diffusion, per example) when testing clinically relevant isolates.…”
Section: Resultsmentioning
confidence: 79%
“…Other available routine tests include epsilometer test and oxacillin agar screening plate. Although recommended by guidelines and validated in multiple studies [1][2][3][4][5][6]8,[12][13][14][15]17,18 , there is a lack of data about the accuracy of these tests in isolates from such a specific population as cystic fibrosis patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation